Heroizability - Ṭāhā, Ibrāhīm (De Gruyter, 2015)
The author argues that Heroizability, the ability of heroizing the major character, is the required theory for producing meanings in literary narratives introduced in three circles: the author's, the protagonist's, and the reader's. Based on an evolutionary model, heroizability treats literary characters as natural anthroposemiotic entities aware of their natural motivation to achieve in order to survive and produce meanings of their survival.
Description based on publisher supplied metadata and other sources
Keywords: Literarische Gestalt; Held; Antiheld; Heroismus; Semiotik